The Who's who of Nobel Prize winners, 1901-2000 - Sherby, Louise S.; Odelberg, Wilhelm (Oryx Press, 2002)
This book is a one-stop source of detailed information on the men and women who earned the Nobel Prize during the 20th century. Organized chronologically by prize, each extensive article contains in-depth information on the laureate's life and career as well as a selected list of his or her publications and biographical resources on the individual. A concise commentary explains why the laureate received the award and summarizes the individual's other important achievements. This completely updated edition also contains a history of the prize. Four indexes distinguish this title from similar biographical references and enable researchers to search by name, education, nationality or citizenship, and religion.